Differentiation of Lynch syndrome from other forms of non-polyposis colorectal cancer among Russian patients - A. S. Tsukanov; N. I. Pospehova; V. P. Shubin; I. Yu. Sachkov; S. N. Zhdankina; A. A. Ponomarenko; E. G. Rybakov; S. I. Achkasov; V. N. Kashnikov; S. A. Frolov; Yu. A. Shelygin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. Lynch's syndrome is hereditary syndrome caused by germline mutation in one of reparation genes not coupled bases and causing high risk of colorectal cancer development. At present there are no criteria, allowing to reveal all mutation carriers, and development of new guidelines is still going on, that became a task for original study. Material and methods. Search of microsatellite instability (MSI), characteristic for Lynch's syndrome, was carried out in tumor samples of 73 patients by fragment analysis method. At its detection search of germline mutations by polymerase chain reaction methods, electrophoresis and direct sequencing was carried out.Results. Microsatellite instability was found out in 17 neoplastic samples (23%, 17 of 73). At 9 person germline mutations that has allowed to attribute this group to patients to Lynch's syndrome were revealed. Three of 9 mutations were described for the first time in the world.Conclusions. According to neoplastic MSI, age and family history two new criteria for Lynch's syndrome search in the Russian patients have been offered. Efficacy of the first criterion was 60%, that of the second — 85,7%.